Fishery, biology and population characteristics of longtail tuna, Thunnus tonggol (Bleeker, 1851) caught along the Indian coast - Abdussamad, E. M. (Indian Journal of Fisheries, 2012)
Fishery, biology and population characteristics of the longtail tuna, Thunnus tonggol were studied during 2006-10. There is no targeted exploitation of the species along the Indian coast. T. tonggol was mainly landed as by-catch in gillnets (63.2 %), hooks and lines (20.3%), ringseines/purseseines (14.9%) and trawls (1.6%). Annual landings during the period varied between 6,073 and 9,140 t with an average of 7,332 t. About 81.5% of the total catch was realized from north-west coast alone. Fishery was supported by fishes of 23 - 111 cm length range with a mean length of 60.5 cm in gillnets. Size at capture was estimated as 51.3 cm and the optimum length for exploitation (Lopt) was 55.3 cm fork length (FL). The length-weight relationship (W = 0.0147 L3.01) indicated isometric growth pattern for the species. The species is non-selective in feeding and feed on pelagic finfishes, crabs and cephalopods. Their size at maturity (Lm) is 51.1 cm and spawns round the year with major peak during October-November. Relative fecundity was 1,32,840 kg body weight-1. Recruitment was almost round the year with peaks during May-June and August-September accounting 53.2% of the total recruitment. Mean size in the catch was larger than optimum size for exploitation; whereas size at capture is much lower, which necessitates caution to increase size at first capture. It can be achieved by increasing the minimum mesh size to 15 cm or more from the present 10/12 cm. Growth parameters of the species were: Lâˆ = 123.5 cm (FL), K = 0.51 year-1 and to= -0.0319 years. Natural mortality (M) was 0.77 y-1, total mortality (Z) 3.72 y-1 and fishing mortality (F) 2.94 y-1. Spawning stock biomass formed 65.4% of the standing stock. Study indicates scope for improving production of the species.